Effect of Chip Mixing Ratio of Pinus pinaster and Populus tremula on Kraft Pulp and Paper Properties - Gülsoy, Sezgin Koray; Tufek, Saduman; Gülsoy, Sezgin Koray (Amer Chemical Soc, 2013)
In this study, Pinus pinaster and Populus tremula chip mixtures were kraft cooked and resulting pulp and paper properties were investigated. The chemical properties and fiber morphology of both species were examined. Cooks were made for five different pine/aspen chip mixtures (0, 25, 50, 75, and 100%). Results of this study showed that pulps with higher kappa number, viscosity, and reject ratio were observed for chips mixtures with higher pine ratio. Higher pine in the mixture resulted in lower total and screened yield. Increase in poplar ratio in mixture gave pulps that were easier to beat. Pine chips improved the strength properties and lowered the brightness and smoothness.
Keywords: Fiber Properties; Histochemical Properties; Lignin; Hardwoods; Guaiacyl